The relationship between students’ mathematical disposition and their learning outcomes - Kamid Kamid; Nizlel Huda; Wardi Syafmen; Sufri Sufri; Sofnidar Sofnidar (Journal of Education and Learning (EduLearn), 2021)
The affective aspects must be owned by students in a lesson, where the affective aspects will have a relationship with the cognitive aspects of a student, therefore this study aimed to determine whether there is a relationship between students 'mathematical dispositions and students' mathematics learning outcomes. Using a mixed method and a sequential explanatory plan, the research was undertaken by first collecting quantitative data and then continuing to collect qualitative data. Where, the sample count in this study was 413 students from junior secondary schools 18 in Jambi City, Indonesia who used a total sampling technique. Data were then analyzed with the help of SPSS 21 application to find descriptive statistics in the form of mean, min, max, and category as well as inferential statistics using Pearson Product Moment. The results obtained in this study dominate both the mathematical disposition of pupils and the learning outcomes of pupils in mathematics. This was reinforced by the existence of a relationship between mathematical disposition and student learning outcomes in mathematics which is indicated by the obtained sig less than 0.05. This means that the mathematical disposition of students which includes the affective aspect of students has a relationship with the cognitive aspect, by having a good affective aspect, the cognitive aspects of the student are also good.